Prispevek k poznavanju prehrane kozače Strix uralensis macroura na Kočevskem - Vrezec, Al (Acrocephalus, 2000)
The article presents an analysis of seven pellets of the Ural Owl Strix uralensis collected in a fir-beech forest Abieti-Fagetum dinaricum in the Kočevsko district, where the owl breeds. 17 prey units items were found, the most common being dormouse Glis glis with 59% proportion by number or 94% proportion by biomass of the prey.
Keywords: Animal nutrition; Birds; ornitologija; ptice; sove